PENDAMPINGAN CALON WIRAUSAHA MIKRO KECIL PADA UPT PEMBERDAYAAN EKONOMI MASYARAKAT (PEM) KOTA CILEGON - Fitriyani, Fara; Suryani, Emma (Universitas Sultan Ageng Tirtayasa, 2016)
The purpose of this study was to provide assistance to small micro business in improving the economy. Through small micro business expected community can have a business that can improve the economic welfare. This study is intended for potential micro entrepreneurs in Citangkil Cilegon City. Problems in program of small micro business is socialization one district one billion Government of Cilegon deemed lacking by most prospective small micro entrepreneurship, the intensity level of mentoring, training, apprenticeship and management consulting low and the level of business growth remained because their lack of knowledge about marketing strategies, business development and / or products.With the help of small micro-entrepreneurs to potential candidates expected the partners got a target in terms of both management and access to capital. Prospective small micro entrepreneurs in need of help both in training, internship, management consulting and marketing.